The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1806-83242011000400009
|View full text |Cite
|
Sign up to set email alerts
|

Bottle feeding, increased overjet and Class 2 primary canine relationship: is there any association?

Abstract: The aim of this study was to investigate the association between bottle feeding and prevalence rates of increased overjet and Class 2 primary canine relationship. The sample consisted of 911 children (461 boys, 450 girls) aged 3 (13.9%), 4 (40.8%), 5 (34%) and 6 (11.3%) years, with complete primary dentition. Information about nutritive and nonnutritive (pacifier and/or digit) sucking habits was collected through questionnaires. Three calibrated dentists (κ: 0.9-1.0 and Rs > 0.90) performed the clinical assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 14 publications
0
31
0
2
Order By: Relevance
“…However, these findings differ from those of most studies in the literature, which have reported sucking habits as the major determinants of the aforementioned anomalies in children. 3,4,11 The design of this study may have favored the finding of this relationship. Cross-sectional studies provide a picture of the moment, and do not offer causality relationships, therefore not being true to reality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these findings differ from those of most studies in the literature, which have reported sucking habits as the major determinants of the aforementioned anomalies in children. 3,4,11 The design of this study may have favored the finding of this relationship. Cross-sectional studies provide a picture of the moment, and do not offer causality relationships, therefore not being true to reality.…”
Section: Discussionmentioning
confidence: 99%
“…Malocclusions have been described as being caused by both geneticevolutionary factors, which may influence the development of the craniofacial complex and of occlusal anomalies, 1,2 and by sucking habits, which may favor the development of these abnormalities. 3,4 According to Nahás-Scocate et al, 5 the key to determine the etiology of malocclusions is to assess the preponderant effect of each factor in particular. The prevalence of this condition in the Brazilian child population has increased progressively, reaching the alarming rate of about 50% of preschoolers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as breastfeeding and non-nutritive sucking habits are associated and showed opposite effects on the prediction of malocclusions 12,21,31 , implementing educational programs and prevention measures in early childhood is essential to reduce the prevalence of malocclusion among preschoolers. Considering that the positive influence of breastfeeding may be masked by the effect of exposure to persistent non-nutritive sucking habits, it is suggested that further studies are planned with a longitudinal design, including a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…2 Parents' education, birth rate, social and economy status, effect of breastfeeding duration to sucking habit and diet influence affects teeth malocclusion on growing children. 3,4 Overjet is a horizontal relationship between maxillary and mandibular incisors. Normal range of overjet is 2-4 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Increased overjet related to class II malocclusion is usually accompanied by class II skeletal sagittal relationship and retrognathia of the mandible. 1,3,4 Overjet which is part of class II division 1 malocclusion is related to two fundamental things about the diagnosis of malocclusion. Increased overjet is the main characteristics of the diagnosis of class II division 1 malocclusion.…”
Section: Introductionmentioning
confidence: 99%